Myostatin and its Regulation: A Comprehensive Review of Myostatin Inhibiting Strategies - Baig, Mohammad Hassan; Ahmad, Khurshid; Moon, Jun Sung; Park, So-Young; Ho Lim, Jeong; Chun, Hee Jin; Qadri, Afsha Fatima; Hwang, Ye Chan; Jan, Arif Tasleem; Ahmad, Syed Sayeed; Ali, Shahid; Shaikh, Sibhghatulla; et al. (Frontiers in Physiology, 2022)
Myostatin (MSTN) is a well-reported negative regulator of muscle growth and a member of the transforming growth factor (TGF) family. MSTN has important functions in skeletal muscle (SM), and its crucial involvement in several disorders has made it an important therapeutic target. Several strategies based on the use of natural compounds to inhibitory peptides are being used to inhibit the activity of MSTN. This review delivers an overview of the current state of knowledge about SM and myogenesis with particular emphasis on the structural characteristics and regulatory functions of MSTN during myogenesis and its involvements in various muscle related disorders. In addition, we review the diverse approaches used to inhibit the activity of MSTN, especially in silico approaches to the screening of natural compounds and the design of novel short peptides derived from proteins that typically interact with MSTN.